DO RETURNS ON HUMAN CAPITAL IMPROVE NIGERIAN ECONOMY? EVIDENCE FROM INTELLECTUAL CAPITAL AND PROPERTY - UZOMBA, PETER CHIKA; IBEINMO, FRIDAY COOKEY (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
This study sets out to investigate if returns on human capital improves the Nigerian economy from 1990 to 2019. Return on human capital herein is proxied as returns on intellectual capital (RITC) and intellectual property (RIPR). Two specific objectives and hypotheses guided the study. Relevant data were sourced from the statistical bulletin of Central Bank of Nigeria and World Bank. The logic of our method of study is drawn from Paul’s Romer Growth and human capital theories as we employ Autoregressive Distributive Lag (ARDL) and residual diagnostic methods for data analysis. The results reveal that RITC makes significant improvement on RGDP, but RIPR fails to do same. This implies that the two measures of human capital do not have the same effect on the Nigerian economy. On this basis, we conclude that returns on intellectual capital are more significant in improving the Nigerian economy than returns on intellectual property. Consequently, we recommend, among others, that the government should protect peoples’ intellectual property by strengthening and reviving the institutions saddled with such responsibilities to sustain and increase the fight against piracy.